A stylistic comparison of Carpathian religious objects particularly with regard to the Greco-Catholic Church in Łosiu - Wójtowicz, Bernadetta (Studia Ecologiae et Bioethicae, 2006)
The article contains a stylistic comparison of the analysis of religious objects and their description of the landscape of the Carpathian region.